Voltage stability assessment of power system network using QV and PV modal analysis - Mohamad Nor, Ahmad Fateh; Sulaiman, Marizan (Faculty of Electronic and Computer Engineering (FKEKK), Universiti Teknikal Malaysia Melaka (UTeM), 2016)
The analysis of voltage instability in electric power system is very crucial in order to maintain the equilibrium of the power system. This paper presents the analysis of voltage instability of electric power system by using reactive power-voltage (QV) and real power-voltage (PV) modal analysis. This research focuses on the voltage instability analysis by implementing the QV and PV modal analysis for mesh-type power system. IEEE 14-bus system has been chosen as the power system. Both QV and PV modal analysis will be run by using MATLAB application software.